Gender Dalam Buku Pendidikan Bahasa Arab Al-`Ashri Kelas X; Studi Analisis Teks Pola Diskriminasi Gender - Mirwan Akhmad Taufiq; Muhimmatul Choiroh (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2020)
AbstractThis article reveals the gender side of the Arabic book "al-Asri class X" which is applied in schools under the auspices of Muhammadiyah East Java. The theme of gender becomes a trending discussion in modern and plural society, this is expected to avoid violence in the social environment of society. This article focuses on studying the patterns and concepts of the presentation of gender-based material, whether gender discrimination is still found in the material or practice questions and even the pictures contained in the book. This research uses descriptive qualitative analysis method with the type of library research, which will explore the research object with a logical description. The findings in this article are the concept of gender in the sample expressed in the form of images and texts with the discovery of the role of injustice between men and women. This can cause gender inequality. Men continue to occupy a central role and women occupy domestic roles. Several forms of discrimination have also been found, including: Stereotypes, Subordination, Marginalization, Double Burden and no Violence patterns found in this book.Keywords: Gender Analysis, Textbooks, Arabic Language Education.